Comparative Mortality of Live Kidney Donors in the UK: 15 Year Cohort Study. (July 2018) - Krishnan, Nithya Santhana; Mumford, Lisa; Lipkin, Graham; Fletcher, Simon; Dasgupta, Indranil; Gill, Paramjit; Ryan, Ronan; Raymond, Neil
Abstract : Aim: To investigate the all-cause mortality experience of U.K live kidney donors in comparison with healthy non-donor controls with up to 15 years follow-up. Methods: Ethics approval was already in place to accrue data from datatbase. Study protocol was reviewed and passed by Renal Registry projects advisory group, and an independent scientific review committee, before release of the data. Cohorts for Study: A) Live Donors (LD) dataset: Dataset obtained from UK Transplant Registry held by National Health Service Blood and Transplant, U.K. All live kidney donors from January 1st 2001 to 31st December, 2013 included and the end date was 31st December 2016 B) Comparative Cohort, The Health Improvement Network (THIN) database: This is a large UK general practice database which contains anonymized longitudinal patient records from over 500 practices. Data from THIN was collected stratified by age, gender and year of entry to provide a large comparator cohort, excluding a number of baseline conditions that would have been a contraindication to donation. Results: Table 1 shows baseline characteristics of LD and THIN. Figure 1 shows a significant difference in mortality between the LD and the THIN cohort, with the LD group doing better. Figure. No caption available. Table 2 showing Cox Proportional hazard Modelling shows that the hazard ratio was significantly more for the THIN group even after adjustments for confounding variables. Further analyses were conducted to examine mortality for different age bands. This showed that there was no difference in 18-29 years age group, but statistically significant differences emerged with longer durations of follow-up in the other age groups; 30-44 years (P= 0.01), 45-59 years (P<0.001) and >60 years (P<0.001). Conclusions: There was no increased risk of mortality in the LD group compared to a healthy cohort on analysis of a 15-year UK database. Warwickshire private Hospitals Charity Grant. Coventry Kidney Research fund, U.K.